2008
DOI: 10.1002/jctb.1871
|View full text |Cite
|
Sign up to set email alerts
|

CO2 absorption into amine solutions: a novel strategy for intensification based on the addition of ferrofluids

Abstract: BACKGROUND: In this paper a novel approach for increasing the mass transfer coefficient in gas/liquid mass transfer is reported and applied to the industrially important system of CO 2 absorption. The approach makes use of a ferrofluid additive to the liquid phase. To demonstrate this strategy, a wetted wall column has been built and experiments have been conducted on the CO 2 /methyl diethanolamine (MDEA) system. This reaction system allows the absorption to be carried out in the transition regime between slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 20 publications
(15 reference statements)
1
43
1
Order By: Relevance
“…Findings of no effect or decreased mass transfer rates for nanofluids in our study is contrary to other studies that report enhanced diffusion or mass transfer in nanofluids [11][12][13][14]. The reasons for this discrepancy are unclear.…”
Section: Interpretation Of Resultscontrasting
confidence: 99%
“…Findings of no effect or decreased mass transfer rates for nanofluids in our study is contrary to other studies that report enhanced diffusion or mass transfer in nanofluids [11][12][13][14]. The reasons for this discrepancy are unclear.…”
Section: Interpretation Of Resultscontrasting
confidence: 99%
“…Uncertainty in the ith independent variable [9][10][11][12][13]. In the case of gas absorption process in nanofluids, most of the researchers have shown that nanoparticles can promote mass transfer coefficient [14][15][16][17][18][19][20]. Although a few studies showed that the mass transport rate in nanofluids is decreased, this can be enhanced with increasing the volume fraction of nanoparticles [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Komati et al [8] have studied the absorption process in CO 2 /MDEA solution by using nanoferrofluid in a wetted-wall column. Their results show an overall enhancement in mass transfer compared to the absence of ferrofluids with a mass transfer coefficient of 92.8% for a 50% volume fraction of the fluid (solid magnetite volume fraction of about 0.39%).…”
Section: Introductionmentioning
confidence: 99%